READER RESPONSE AND MORAL AMBIGUITY IN YOUNG ADULT DYSTOPIAN FICTION - Daniel Thompson (International Journal of Literature and Language Studies, 2026)
This article investigates how young readers respond to moral ambiguity in contemporary dystopian fiction. The study responds to the problem that young adult dystopias are often praised for social criticism, yet less attention is paid to how readers interpret ethically uncertain choices made by protagonists. Using qualitative reader-response analysis focused on interpretive patterns, the article analyzes reading journals and group discussions from students responding to three dystopian novels. The findings indicate that readers did not simply classify characters as heroes or villains; instead, they connected moral ambiguity to survival, institutional violence, and responsibility to community. The article argues that dystopian fiction can support ethical literacy by inviting students to debate conflicting values rather than memorize fixed moral lessons. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.